2021
DOI: 10.1093/ofid/ofab417
|View full text |Cite
|
Sign up to set email alerts
|

Addressing and Inspiring Vaccine Confidence in Black, Indigenous, and People of Color During the Coronavirus Disease 2019 Pandemic

Abstract: During the COVID-19 pandemic, we have witnessed profound health inequities suffered by Black, Indigenous, and People of Color (BIPOC). These manifested as differential access to testing early in the pandemic, rates of severe disease and death 2-3 times higher than White Americans, and now, significantly lower vaccine uptake compared with their share of the population affected by COVID-19. This article explores the impact of these COVID-19 inequities (and the underlying cause, structural racism) on vaccine acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0
9

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 37 publications
2
40
0
9
Order By: Relevance
“…Overall vaccinations rates and patterns over time in Black and Hispanic populations and high SVI zip codes further underscores the deeply embedded systemic nature of racialized disparities and the highly intersectional nature of systemic racism and social vulnerability [1,[27][28][29][30][33][34][35]. Even though several vaccination strategies sought to prioritize Black and Hispanic individuals living in high SVI zip codes given their high burden of disease earlier on [11,12,[36][37][38], they still had dramatically lower vaccination rates compared to White and Asian individuals in the same high SVI zip codes and those from zip codes with low SVIs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Overall vaccinations rates and patterns over time in Black and Hispanic populations and high SVI zip codes further underscores the deeply embedded systemic nature of racialized disparities and the highly intersectional nature of systemic racism and social vulnerability [1,[27][28][29][30][33][34][35]. Even though several vaccination strategies sought to prioritize Black and Hispanic individuals living in high SVI zip codes given their high burden of disease earlier on [11,12,[36][37][38], they still had dramatically lower vaccination rates compared to White and Asian individuals in the same high SVI zip codes and those from zip codes with low SVIs.…”
Section: Discussionmentioning
confidence: 99%
“…These patterns must also be contextualized within the growing literature on vaccine confidence and hesitancy. Vaccine hesitancy is not monolithic and ranges from beliefs in conspiracy theories and skepticism about COVID-19 to more nuanced concerns regarding safety, side effects, inability to take time off work, observing others safely vaccinated (i.e., social proof), and lack of trusted messaging [29,[33][34][35][40][41][42]; its patterns and trends across communities also varies [43,44]. Qualitative studies have shown that lack of vaccine confidence in Black communities in particular stems largely from histories of systematic mistreatment and racism-which includes failed contemporary responses to COVID-19-leading to mistrust of larger institutions and concerns over bearing the burden of unfavorable safety and side effect profiles (particularly given the rapid timeline of development and shifting messaging over the need for additional doses) [29,35].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It should be noted that the rates of infection, hospitalization, and death from COVID-19 in Black 40 , Hispanic 41 , and American Indian/Alaska Native communities 42 have been disproportionately higher than other racial or ethnic groups. The role of biology and disproportionate prevalence of medical comorbidities has not been enough to explain these inequities, in addition to a wealth of data suggesting that these differences are driven by social and structural vulnerabilities resulting from the impacts of structural racism in these communities 43 , 44 . Additional details of inequities seen with COVID-19 will be presented later in this collection (Chapter 4).…”
Section: Host Immune Responsesmentioning
confidence: 99%